KEPENTINGAN EKONOMI POLITIK TIONGKOK MELAKUKAN KERJASAMA DENGAN RUSIA DI WILAYAH ARKTIK TAHUN 2012-2015 - Tiara Nanda Ademuty; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research describes the economy politics interest of Tiongkok to cooperate with Rusia in Artic Seas in 2012-2015. Artic sea are one of high seas in world that have big potenciall in oil, fuel and fauna flora. Artic seas have deacleared by five country as a Council Institution likes United States America. Norwegia, Swedia, Canada and Rusia. Tiongkok use a Rusia to get the exploration rights in Artic Seas.The writer collects data from books, encyclopedia, journal, mass media and websites to analyze the economy politics interest of Tiongkok to cooperate with Rusia in Artic Seas. The theories applied in this research are neoliberalisme perspective with the international cooperation theory.The conclusion of this research are the economy politics interest of Tiongkok to cooperate with Rusia in Artic Seas cause economic factors are to opened the trade sea ways from Tiongkok to Eropa countries, needed of Tiongkok oil‟s, Tiongkok get a rexploration right in Artic Seas. And the political interest of Tiongkok in Artic Seas likes security region interest, increase of hegemony Tiongkok in Artic Seas, to protect hegemony in United States in Artic Seas and Tiongkok do a research in Artic about environmental issues.Key words: economy, politics, interes and artic.